Effect of Preemptive Ketamine Administration on Postoperative Visceral Pain after Gynecological Laparoscopic Surgery - 林洪启 贾东林 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
The pain following gynecological laparoscopic surgery is less intense than that following open surgery; however, patients often experience visceral pain after the former surgery. The aim of this study was to determine the effects of preemptive ketamine on visceral pain in patients undergoing gynecological laparoscopic surgery. Ninety patients undergoing gynecological laparoscopic surgery were randomly assigned to one of three groups. Group 1 received placebo. Group 2 was intravenously injected with preincisional saline and local infiltration with 20 m L ropivacaine（4 mg/m L） at the end of surgery. Group 3 was intravenously injected with preincisional ketamine（0.3 mg/kg） and local infiltration with 20 m L ropivacaine（4 mg/m L） at the end of surgery. A standard anesthetic was used for all patients, and meperidine was used for postoperative analgesia. The visual analogue scale（VAS） scores for incisional and visceral pain at 2, 6, 12, and 24 h, cumulative analgesic consumption and time until first analgesic medication request, and adverse effects were recorded postoperatively. The VAS scores of visceral pain in group 3 were significantly lower than those in group 2 and group 1 at 2 h and 6 h postoperatively（P〈0.05 and P〈0.01, respectively）. At 2 h and 6 h, the VAS scores of incisional pain did not differ significantly between groups 2 and 3, but they were significantly lower than those in group 1（P〈0.01）. Groups 1 and 2 did not show any differences in visceral pain scores at 2 h and 6 h postoperatively. Moreover, the three groups showed no statistically significant differences in visceral and incisional pain scores at 12 h and 24 h postoperatively. The consumption of analgesics was significantly greater in group 1 than in groups 2 and 3, and the time to first request for analgesics was significantly longer in groups 2 and 3 than in group 1, with no statistically significant difference between groups 2 and 3. However, the three groups showed no significant difference in the incidence of shoulder pain or adverse effects. Preemptive ketamine may reduce visceral pain in patients undergoing gynecological laparoscopic surgery.